EVALUATION OF CUTANEOUS ADVERSE DRUG REACTIONS IN A TERTIARY CARE HOSPITAL IN SOUTHERN INDIA: A RETROSPECTIVE ANALYSIS - ANKITA PANIGRAHY; ASIYA BEGUM; USHARANI PINGALI; MEKALA PADMAJA; AMAL SAJEEV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study was undertaken to understand the demographic profile, common causative drugs, and the presentations of cutaneous adverse drug reactions (CADR) among the patients of our hospital. Methods: This is a retrospective analytical study. All CADR reported to our adverse drug reaction monitoring center from dermatology outpatient department (OPD), other OPDs, intensive care units, and inpatient wards of our hospital from September 2022 to March 2024 was collected from VIGIFLOW (software used by the pharmacovigilance program of India). The data was then analyzed. Results: A total of 272 CADR were reported over the study period. The median age of presentation was 41 years (Interquartile range=23). Overall 44 (16.18%) serious and 228 (83.82%) non-serious CADR were reported. Erythematous maculopapular rash was the most common clinical presentation (63%). Bullous exfoliative drug eruptions and Stevens Johnson’s syndrome were some of the serious CADR. The most common suspected medications were antibiotics (42.15%) followed by non-steroidal anti-inflammatory drugs (8.92%). In 76% of the cases, the suspected medication was withdrawn. The outcome was reported as “Recovering” in 52% of the cases. On causality assessment, 251 (92%) CADR were classified as “Possible.” Conclusion: A CADR is a common yet preventable health problem. As seen from our study, most of the suspected medications were withdrawn and subsequently the patients were recovering from the CADR. Hence, early diagnosis, identification, and withdrawal of the implicating drugs help in timely recovery and prevention of complications, which in turn help in decreasing the burden on our healthcare system.